Cobalt in Nitrogen-Doped Graphene as Single-Atom Catalyst for High-Sulfur Content Lithium–Sulfur Batteries - Du, Zhenzhen; Chen, Xingjia; Hu, Wei; Chuang, Chenghao; Xie, Shuai; Hu, Ajuan; Yan, Wensheng; Kong, Xianghua; Wu, Xiaojun; Ji, Hengxing; Wan, Li-Jun (Journal of the American Chemical Society, 2019)
Because of their high theoretical energy density and low cost, lithium–sulfur (Li–S) batteries are promising next-generation energy storage devices. The electrochemical performance of Li–S batteries largely depends on the efficient reversible conversion of Li polysulfides to Li2S in discharge and to elemental S during charging. Here, we report on our discovery that monodisperse cobalt atoms embedded in nitrogen-doped graphene (Co–N/G) can trigger the surface-mediated reaction of Li polysulfides. Using a combination of operando X-ray absorption spectroscopy and first-principles calculation, we reveal that the Co–N–C coordination center serves as a bifunctional electrocatalyst to facilitate both the formation and the decomposition of Li2S in discharge and charge processes, respectively. The S@Co–N/G composite, with a high S mass ratio of 90 wt %, can deliver a gravimetric capacity of 1210 mAh g–1, and it exhibits an areal capacity of 5.1 mAh cm–2 with capacity fading rate of 0.029% per cycle over 100 cycles at 0.2 C at S loading of 6.0 mg cm–2 on the electrode disk.